HUBUNGAN FAKTOR RISIKO DERMATITIS KONTAK PADA PETANI - Rahmatika, Achisna; Saftarina, Fitria; Anggraini, Dwi Indria; Mayasari, Diana (Jurnal Kesehatan, 2020)
About 30% of occupational diseases in farmers are contact dermatitis. Contact dermatitis due to work in the agricultural sector is the main commodity in Lampung Province at 35,82%. Farmers are generally always exposed to chemicals in the form of pesticides and fertilizers which can be irritants and allergens. This research was an observational descriptive using a cross-sectional method with 379 respondents. The research data were taken from interviews, questionnaires, and physical examinations by dermatologists and genitals. Data were analyzed using the chi-square test. Results: 13,5% of farmers experienced contact dermatitis. The analysis results of this study indicate that there is a statistical relationship between contact dermatitis with the use of the following factors, personal protective equipment (p-value=0,000), contact time (p-value=0,000), personal hygiene (p-value=0,000), total types of pesticides (p-value=0,000), and number of types of fertilizer (p-value=0,000). While the factors that were not statistically significant in this study were the relationship between contact dermatitis and length of service (p-value=0,919), atopic history (p-value=0,784), and type of occupation (p-value=0,115). There is a relationship between the following factors such as the use of personal protective equipment, duration of contact, personal hygiene, the number of pesticides, and the number of types of fertilizers with the incidence of contact dermatitis in farmers in the District of Punduh pedada.